2007
DOI: 10.1002/bem.20311
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of head‐movements in stray fields generated by a 7 Tesla whole‐body MRI magnet

Abstract: The study investigates the impact of exposure to the stray magnetic field of a whole-body 7 T MRI scanner on neurobehavioral performance and cognition. Twenty seven volunteers completed four sessions, which exposed them to approximately 1600 mT (twice), 800 mT and negligible static field exposure. The order of exposure was assigned at random and was masked by placing volunteers in a tent to hide their position relative to the magnet bore. Volunteers completed a test battery assessing auditory working memory, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 24 publications
2
61
1
1
Order By: Relevance
“…However, the estimate of average effect was smaller (-0.7%/100 mT) than the estimates from individual studies (-3%/100 mT and -1.3%/100 mT, respectively, (13,14)), which can be attributed to the fact that the posterior summarization is based on the measurement data and the assumed prior distribution.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, the estimate of average effect was smaller (-0.7%/100 mT) than the estimates from individual studies (-3%/100 mT and -1.3%/100 mT, respectively, (13,14)), which can be attributed to the fact that the posterior summarization is based on the measurement data and the assumed prior distribution.…”
Section: Discussionmentioning
confidence: 72%
“…It should be noted, however, that these exposure-response analysis, assuming a linear association, implies that at an exposure of 1600 mT, which can be achieved in close proximity to a 7-T cylindrical magnet (14), performance will be reduced with ϳ16%. Furthermore, the use of interventional procedures guided by MRI is increasing dramatically and involves delicate procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will allow the scientific community to assess whether these data indeed point to an absence of cognitive effects after exposure to static magnetic fields (SMF), or whether this is primarily a problem with statistical power. Although conducted at lower field strengths, results from similar studies among 17-40 human volunteers (3)(4)(5)(6) suggested that most likely 25 subjects was insufficient to detect any effects (after adjustment for learning effects) still present several minutes after exposure. However, information on the distributions and results from power calculations are needed to be able to properly assess this aspect.…”
mentioning
confidence: 99%